ELECTRICITY INSTALLATION SKILLS TRAINING IN RINONDORAN VILLAGE COMMUNITY, LIKUPANG EAST MINAHASA SUB-DISTRICT, NORTH MINAHASA - F J Tasiam (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2020)
This service aims to create jobs in the field of repairing and installing electrical installations in Rinondoran village, Likupang sub-district, East Minahasa Utara. The target audiences in this training are families in place to repair / revise electrical installations in community homes, community leaders, religious leaders, government in the village, PKK leaders, in general this skills training is directed at all communities in Rinondoran Village. Likupang Timur District, Minahasa Utara North Sulawesi The method used in this training is the direct experimental method, namely directly repairing / revising from house to house in the Rinondoran community of East Likupang District. While repairing / revising explains the cause and effect of the damage The result of this dedication. The community can do the electricity installation well, not only in their village, but in other villages. This can increase income in his village.